Cognitive deterioration in adult epilepsy: clinical characteristics of "Accelerated Cognitive Ageing". (28th October 2016) - Breuer, L. E. M.; Grevers, E.; Boon, P.; Bernas, A.; Bergmans, J. W. M.; Besseling, R. M. H.; Klooster, D. C. W.; de Louw, A.; Mestrom, R. M. C.; Vonck, K.; Zinger, S.; Aldenkamp, A. P.
Abstract : Objectives: "Epileptic dementia" is reported in adults with childhood‐onset refractory epilepsy. Cognitive deterioration can also occur in a "second‐hit model". Materials and methods: We studied the clinical and neuropsychological characteristics of patients with cognitive deterioration (≥1 SD discrepancy between current IQ and premorbid IQ). Memory function, reaction time and processing speed were also evaluated. Analyses were performed to investigate which clinical characteristics correlated with cognitive deterioration. Results: Twenty‐seven patients were included with a mean age of 55.7 years old, an average age at epilepsy onset of 33.9 years and a mean duration of 21.8 years. Over 40% had experienced at least one status epilepticus. About 77.8% had at least one comorbid disease (most of (cardio)vascular origin). Cognitive deterioration scores were significant for both Performance IQ and Full Scale IQ, but not for Verbal IQ. Impairments in fluid functions primarily affected the IQ‐scores. Memory was not impaired. Epilepsy factors explained 7% of the variance in deterioration, whereas 38% was explained by relatively low premorbid IQ and educational level, high age at seizure onset and older age. Conclusions: A subgroup of patients with localization‐related epilepsy exhibits cognitive decline characterized by deterioration in PIQ and FSIQ, but with preserved higher order functions (VIQ and memory). Patients typically have epilepsia tarda, comorbid pathology, relatively low educational level and older age. These are factors known to increase the vulnerability of the brain by diminishing cognitive reserve. Cognitive deterioration may develop according to a stepwise "second‐hit model", affecting and accelerating the cognitive ageing process.